2020
DOI: 10.3390/brainsci10020065
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells/Neuronal Precursor Cells and Postmitotic Neuroblasts in Constitutive Neurogenesis and After ,Traumatic Injury to the Mesencephalic Tegmentum of Juvenile Chum Salmon, Oncorhynchus keta

Abstract: The proliferation of neural stem cells (NSCs)/neuronal precursor cells (NPCs) and the occurrence of postmitotic neuroblasts in the mesencephalic tegmentum of intact juvenile chum salmon, Oncorhynchus keta, and at 3 days after a tegmental injury, were studied by immunohistochemical labeling. BrdU+ constitutive progenitor cells located both in the periventricular matrix zone and in deeper subventricular and parenchymal layers of the brain are revealed in the tegmentum of juvenile chum salmon. As a result of trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 58 publications
9
46
2
Order By: Relevance
“…Their ontogenesis is characterized by such phenomena as developmental delay and retention of signs of the embryonic organization of CNS which occur at the stage of active brain growth, where the morphogenesis processes are most clearly and fully expressed [ 11 ]. This feature of salmon CNS development, referred to as embrionalization, is confirmed by the presence of a large number of embryonic neuronal stem cells (NSCs) corresponding to cells of the neuroepithelial (NE) type, as well as radial glial (RG) cells corresponding to adult progenitors [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their ontogenesis is characterized by such phenomena as developmental delay and retention of signs of the embryonic organization of CNS which occur at the stage of active brain growth, where the morphogenesis processes are most clearly and fully expressed [ 11 ]. This feature of salmon CNS development, referred to as embrionalization, is confirmed by the presence of a large number of embryonic neuronal stem cells (NSCs) corresponding to cells of the neuroepithelial (NE) type, as well as radial glial (RG) cells corresponding to adult progenitors [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the proliferative zones of the telencephalon of juvenile O. masou [ 15 ] and the mesencephalic tegmentum of juvenile chum salmon O. keta [ 14 ], vimentin is present in NE cells and is not detected in the RG of intact animals. Studies of the immunolabeling of nestin in the tegmentum of juvenile O. keta have also shown its presence in NE cells located both in the periventricular zone (PVZ) and in the tegmental parenchyma, as well as the presence of widespread Nes+ granules in the mesencephalic reticular formation in intact juvenile chum salmon [ 14 ]. After a traumatic brain injury (TBI), Vim+ RG appears in the telencephalon of juvenile O. masou and O. keta and is absent in intact animals [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations